Children's Green Infrastructure: Children and Their Rights to Nature and the City - Vidal, Diogo Guedes; Castro Seixas, Eunice (Frontiers in Sociology, 2022)
The development of green spaces in cities has corresponded to a need to deal with a series of socio-environmental and health problems felt in urban spaces. However, these are often fragmented or somewhat disconnected interventions that leave out vulnerable and subaltern groups like children, being also commonly based on strictly formatted designs, with more urban furniture than natural elements. In view of the need to make urban spaces healthier, safer, more resilient, and at the same time more child-friendly, in this Conceptual Analysis paper we build from the literature on Urban Green Spaces, Child-Friendly Cities and environments, and Children’s Infrastructure to propose the concept of Children Green Infrastructure (CGI), and discuss its application to urban planning, foregrounding the need for fairer, more inclusive and participatory approaches. GGI derives from the Children Infrastructure concept but it puts at the center of the debate the idea of connecting children to nature where they live, learn and play. CGI is based on the assumption that nature should be transversal in urban planning processes, and that it must be perfectly integrated within urban infrastructures, ensuring access to all. Understanding children’s needs and integrating their voices in urban planning and design processes are necessary conditions to moving forward to a fairer, more inclusive and truly collective urban project.